Online analysis of H2S and SO2 via advanced mid-Infrared gas sensors - Petruci, João Flavio da Silveira [UNESP]; Wilk, Andreas; Cardoso, Arnaldo Alves [UNESP]; Mizaikoff, Boris (American Chemical Society (ACS), 2015)
Volatile sulfur compounds (VSCs) are among the most prevalent emitted pollutants in urban and rural atmospheres. Mainly because of the versatility of sulfur regarding its oxidation state (2- to 6+), VSCs are present in a wide variety of redox-environments, concentration levels, and molar ratios. Among the VSCs, hydrogen sulfide and sulfur dioxide are considered most relevant and have simultaneously been detected within naturally and anthropogenically caused emission events (e.g., volcano emissions, food production and industries, coal pyrolysis, and various biological activities). Next to their presence as pollutants, changes within their molar ratio may also indicate natural anomalies. Prior to analysis, H2S- and SO2-containing samples are usually preconcentrated via solid sorbents and are then detected by gas chromatographic techniques. However, such analytical strategies may be of limited selectivity, and the dimensions and operation modalities of the involved instruments prevent routine field usage. In this contribution, we therefore describe an innovative portable mid-infrared chemical sensor for simultaneously determining and quantifying gaseous H2S and SO2 via coupling a substrate-integrated hollow waveguides (iHWG) serving as a highly miniaturized mid-infrared photon conduit and gas cell with a custom-made preconcentration tube and an in-line UV-converter device. Both species were collected onto a solid sorbent within the preconcentrator and then released by thermal desorption into the UV-device. Hydrogen sulfide is detected by UV-assisted quantitative conversion of the rather weak IR-absorber H2S into SO2, which provides a significantly more pronounced and distinctively detectable rovibrational signature. Modulation of the UV-device system (i.e., UV-lamp on/off) enables discriminating between SO2 generated from H2S conversion and abundant SO2 signals. After optimization of the operational parameters, calibrations in the range of 0.75-10 ppmv with a limit of detection (LOD) at 77 ppbv for SO2 and 207 ppbv for H2S were established after 20 min of sampling time at 200 mL min(-1). Taking advantage of the device flexibility in terms of sampling time, flow-rate, and iHWG design facilitates tailoring the developed Preconcentrator-UV-device-iHWG device toward a wide variety of application scenarios ranging from environmental/atmospheric monitoring to industrial process monitoring and clinical diagnostics.